THE ANALYSIS OF OPTIMAL CRACK RATIO FOR PWR PRESSURE VESSEL CLADDING USING GENETIC ALGORITHM - Susmikanti, Mike; Himawan, Roziq; Sulistyo, Jos Budi (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2018)
Several aspects of material failure have been investigated, especially for materials used in Reactor Pressure Vessel (RPV) cladding. One aspect that needs to be analyzed is the crack ratio. The crack ratio is a parameter that compares the depth of the gap to its width. The optimal value of the crack ratio reflects the material's resistance to the fracture. Fracture resistance of the material to fracture mechanics is indicated by the value of Stress Intensity Factor (SIF). This value can be obtained from a J-integral calculation that expresses the energy release rate. The detection of the crack ratio is conducted through the calculation of J-integral value. The Genetic Algorithm (GA) is one way to determine the optimal value for a problem. The purpose of this study is to analyze the possibility of fracture caused by crack. It was conducted by optimizing the crack ratio of AISI 308L and AISI 309L stainless steels using GA. Those materials are used for RPV cladding. The minimum crack ratio and JIntegral values were obtained for AISI 308L and AISI 309L. The SIF value was derived from the JIntegral calculation. The SIF value was then compared with the fracture toughness of those material. With the optimal crack ratio, it can be predicted that the material boundaries are protected from damaged events. It can be a reference material for the durability of a mechanical fracture event.